2020
DOI: 10.1590/1413-785220202803228291
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Periarticular Hyaluronic Acid Infiltration for the Treatment of Lateral Epicondylitis

Abstract: Objective: To prospectively, clinically and functionally follow-up patients previously diagnosed with lateral epicondylitis after periarticular application of hyaluronic acid and analyze the results. Methods: All patients were previously treated conservatively and had no clinical improvement. Data such as age, positivity for specific tests (Cozen and Mill), visual analogue pain scale (VAS) before and during dorsiflexion of the wrist with resistance, diagnosis time, Mayo Elbow Performance Score was collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
1
1
Order By: Relevance
“…However, VAS for pain decreases in this study were smaller than the minimum clinically important improvement [21]. Contrarily, another study showed a high rate of failure in treatment (25%) when periarticular hyaluronic infiltration was used for resistant cases of lateral epicondylitis [22].…”
Section: Discussioncontrasting
confidence: 60%
“…However, VAS for pain decreases in this study were smaller than the minimum clinically important improvement [21]. Contrarily, another study showed a high rate of failure in treatment (25%) when periarticular hyaluronic infiltration was used for resistant cases of lateral epicondylitis [22].…”
Section: Discussioncontrasting
confidence: 60%
“…Stirma и соавт. [16], изучавших действие этого препарата при ЛЭ (n=52): средняя интенсивность боли при движении после курса ЛИТ ГлК снизилась с 8,1 до 3,6 см по ВАШ.…”
Section: Days Apart) Under Ultrasound Guidance Treatment Results Were...unclassified
“…HA, which was first isolated in the 1930s, is a distinctive glycosaminoglycan, which, unlike other glycosaminoglycans such as heparan sulphate, chondroitin sulphate, and keratan sulphate, is non-sulphated [52]. It is widely used in treating osteoarthritis [36,[53][54][55][56][57][58] and in tissue-engineering approaches for disc repair [59,60]. HA ( Figure 3) is an abundant polymer of the ECM with a molecular weight of approximately 10 6 -10 7 Da in vivo [61].…”
Section: Hyaluronic Acid In Treating the Ivd: Structure Synthesis Anmentioning
confidence: 99%